1994
DOI: 10.1038/clpt.1994.50
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis for differences in debrisoquin polymorphism between a spanish and other white populations

Abstract: The debrisoquin hydroxylation polymorphism is an autosomic recessive trait of the cytochrome P450IID6, an enzyme involved in drug metabolism, that affects 5% to 10% of white subjects. The genetic basis of this polymorphism was studied in 258 unrelated Spanish white subjects. The results revealed that about 5% of the subjects were homozygous for mutant alleles and that about 1% of the subjects carried alleles that suggested CYP2D6 gene duplication. The extensive metabolizers who were homozygous for the wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 0 publications
8
23
1
Order By: Relevance
“…In Caucasians the frequency of allele *4 is 19% whereas in the present study it was found to be 14%. 3,9 Allele *5 has been found at frequencies between 2 and 4% in Caucasians, 3,10 which resembles our findings (3.3%). In our sample these four alleles (*3, *4, *5 and *6) accounted for 100% of CYP2D6 defective alleles.…”
Section: Discussionsupporting
confidence: 91%
“…In Caucasians the frequency of allele *4 is 19% whereas in the present study it was found to be 14%. 3,9 Allele *5 has been found at frequencies between 2 and 4% in Caucasians, 3,10 which resembles our findings (3.3%). In our sample these four alleles (*3, *4, *5 and *6) accounted for 100% of CYP2D6 defective alleles.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of these allelic variants is similar to that found in the general Spanish population [47,48], This genetic polymorphism has been studied in other neurological disorders. It is widely admit ted that carriers of the genotype CYP2D6*1/CYP2D6*4 show increased risk for PD [7][8][9].…”
Section: Discussionsupporting
confidence: 50%
“…The findings indicate that CYP2D6*5 in most cases is combined with the CYP2D6*1 allelic variant in the other chromosome. The frequency of CYP2D6 variants at the complementary gene in the subgroup of carriers of CYP2D6*5 was similar to the CYP2D6 allele frequency among unrelated Spaniard noncarriers of CYP2D6*5 (6,8 ). We therefore observed no association between CYP2D6*5 and mutations in the complementary gene.…”
Section: Resultsmentioning
confidence: 47%
“…Genomic DNA was purified from peripheral leukocytes and kept in sterile plastic vials at 4°C until analysis. We performed the CYP2D6 genotyping analysis by mutation-specific PCR, long PCR, and restriction mapping with the enzymes EcoRI and XbaI as described elsewhere (8,(13)(14)(15)(16). For the sequencing analyses of exons 1-9 and the 3Јflanking region of CYP2D8P, we conducted a series of 12 PCR amplification reactions spanning areas of ϳ0.5 kb between the positions Ϫ25 (CYP2D8P) and Ϫ276 (the 3Ј intergenic region of CYP2D8P).…”
Section: Methodsmentioning
confidence: 99%